Knockout of Toll-Like Receptors 2 and 4 Prevents Renal Ischemia-Reperfusion-Induced Cardiac Hypertrophy in Mice. - Mayra Trentin-Sonoda; Rogério Cirino da Silva; Fernanda Vieira Kmit; Mariana Vieira Abrahão; Gustavo Monnerat Cahli; Guilherme Visconde Brasil; Humberto Muzi-Filho; Paulo André Silva; Fernanda Freire Tovar-Moll; Adalberto Vieyra; Emiliano Medei; Marcela Sorelli Carneiro-Ramos (PLoS ONE, 2015)
We investigated whether the pathways linked to Toll-like receptors 2 and 4 (TLRs) are involved in renal ischemia-reperfusion (I/R)-induced cardiac hypertrophy. Wild type (WT) C57BL/6J, TLR2-/- and TLR4-/- mice were subjected to left kidney ischemia for 60 min followed by reperfusion for 5, 8, 12 and 15 days. Proton density magnetic resonance showed alterations in the injured kidney from WT mice, together with signs of parenchymal edema and higher levels of vimentin mRNA, accompanied by: (i) small, but significant, increase in serum urea after 24 h, (ii) 100% increase in serum creatinine at 24 h. A serum peak of inflammatory cytokines occurred after 5 days of reperfusion. Heart weight/body weight and heart weight/tibia length ratios increased after 12 and 15 days of reperfusion, respectively. Cardiac hypertrophy markers, B-type natriuretic peptide (BNP) and α-actin, left ventricle mass, cardiac wall thickness and myocyte width increased after 15 days of reperfusion, together with longer QTc and action potential duration. Cardiac TLRs, MyD88, HSP60 and HSP70 mRNA levels also increased. After 15 days of reperfusion, absence of TLRs prevented cardiac hypertrophy, as reflected by similar values of left ventricular cardiac mass and heart weight/body weight ratio compared to the transgenic Sham. Renal tissular injury also ameliorated in both knockout mice, as revealed by the comparison of their vimentin mRNA levels with those found in the WT on the same day after I/R. The I/R TLR2-/- group had TNF-α, IFN-γ and IL-1β levels similar to the non-I/R group, whereas the TLR4-/- group conserved the p-NF-κB/NF- κB ratio contrasting with that found in TLR2-/-. We conclude: (i) TLRs are involved in renal I/R-induced cardiac hypertrophy; (ii) absence of TLRs prevents I/R-induced cardiac hypertrophy, despite renal lesions seeming to evolve towards those of chronic disease; (iii) TLR2 and TLR4 selectively regulate the systemic inflammatory profile and NF- κB activation.